Pengembangan Sistem Informasi Autopsi Verbal (Studi Kasus : Dinas Kesehatan Kabupaten Malang) - Muhammad Ridho; Ismiarta Aknuranda; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Malang District's health service offices own a pilot project whose objective is to record in the form of causes of death in the region Gondanglegi and Kepanjen. One of the ways to record such data is through verbal autopsy which is done by interviewing family members of the deceased on visible signs or symptoms of a certain individual before death. The ongoing process of the verbal autopsy is still recorded manually using paper, which when gathered is vulnerable to being lost or damaged. Otherwise, there was no system to record the data that has been gathered. Based on the above-mentioned problem, an information system is needed to ease the recording, storing, and processing of data that contains verbal autopsy. The development of the information system uses a prototyping method which presents a picture of the system in general toward the client in order to gain feedback in the form of advice or critique. Development is started with the modeling of the business process and requirements of the analysis, prototype designing, prototype evaluation, continued designing, which is finished with implementation and testing. The implementation results in a web-based verbal autopsy information system. The system is utilized to record, verify, manage, and manage verbal autopsy data and to present general information. The next step is to test the implementation results with validation testing which shows valid test results which are in accord with the identified requirements, tests towards the compatibility of the browser show that the error issues were at 9% and the system was run on a variety of browsers without any problems whatsoever.